Social Media in ESL Classroom: Teachers’ Preference and Challenges - Poh Xian, Gan; Md Yunus, Melor (International Journal of Academic Research in Progressive Education and Development, 2023)
The advancement of technology has brought us convenience to keep up with the world. With a click of the gadgets, it bridges us with people and recent happenings in the society. Social media platforms have been one of the most popular software-based digital technologies that are widely utilized, including educators who teach skills and deliver knowledge in the classroom. Numerous research had been conducted to provide insights and professional practices to the educators. However, a few has been done in Malaysia semi-urban primary ESL (English as a Second Language) classroom context. Thus, this research was intended to explore the use of social media platforms in primary ESL classroom. An online survey questionnaire which presented in Google Form had been distributed to 300 primary ESL teachers in Terengganu, Malaysia to know their most preferred social media platform and challenges faced in ESL classroom. The result showed that YouTube is the most preferred social media platform in ESL teaching. It also portrayed that the most challenging issue was time constraint. It is recommended to conduct a detailed research to understand the real-world situation by having in-depth interviews with the ESL teachers to discover their ESL teaching experience in using social media platforms.